The Barbados-Panama conncetion revisited : commemorating migration fron Barbados to Panama 1904-1914 - Newton, Velma Barbados Museum & Historical Society, National Cultural Foundation and the Department of History and Philosophy, UNiversity of the West Indies, Cave Hill Campis; Drayton, Kathleen; Marshall, Woodville (Estados Unidos de América : A&A Printing, 2014)
Barbadians were the largest group of labourers recruited by the Amerivan canal builders, for construction of the Panama Canal between 1904-1914.
TABLE OF CONTENTS ACKNOWLEDGEMENTS NOTES ON CONTRIBUTORS INTRODUCTION WHY A PANAMA CANAL? BACKGROUND TO PANAMA MIGRATION ORGANISING THE MIGRATION THE PANAMA MAN PHOTOGRAPHS THE MIGRANT'S POST CANAL STORY POLITICS AND EROSION OF THE WEST INDIAN SUBCULTURE PANAMA MONEY AND LAND ACQUISITION APPENDIX BIBLIOGRAPHY
La obra fue autografiada y entregada por la autora Velma Newton, el 18 de agosto de 2014.
Keywords: BARBADOS -- HISTORIA; PANAMÁ -- HISTORIA; CANAL DE PANAMÁ; THE PANAMA CANAL